Respuesta :
Answer:f(x) = a(x – h)² + k
we know the vertex v(5,3)
substitute in the values for h and k
f(x) = a(x – 5)² + 3
Use another point and substitute in values for x and f(x).
for the point (6,5)
Solve for a.
5 = a(6 – 5)2 + 3-------------- > 5=a+3-------------> a=2
The function is f(x)=a(x – h)2 + k-------- > 2(x – 5)² + 3
f(x)= 2(x – 5)² + 3-------- > 2[x²-10x+25]+3=2x²-20x+50+3=2x²-20x+53
f(x)=2x²-20x+53
the answer is f(x)= 2(x – 5)² + 3----------------- > (f(x)=2x²-20x+53)
Step-by-step explanation:
Answer:
yes, the answers are as follow:
first 2
second 5
last 3
forming f(x) = 2(x-5)^2 + 3
Step-by-step explanation:
got it right in edg 2020 hope this is of help :)